2018
DOI: 10.1111/1753-0407.12861
|View full text |Cite
|
Sign up to set email alerts
|

Concentrated insulins: History and critical reappraisal

Abstract: The earliest marketed insulins were crude acidic formulations with concentrations of ≤10 units/mL. Since the early 1920s, insulins have improved continually, via bioengineering, process, and chemical modifications. Today, most insulin formulations have a concentration of 100 units/mL (U100). However, more concentrated insulin formulations (200, 300, and 500 units/mL; U200, U300, and U500, respectively) are also available. There is a tendency to assume that concentrated insulins are similar, both to each other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…Endocrinologists, rheumatologists, gastroenterologists, and dermatologists have been prescribing biologics for at-home injection for many years. The best-known example, insulin, has been in use for nearly 100 years 24. At-home self-administration has the potential to reduce the burden on specialty clinics and allow physicians time to treat more patients with severe asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Endocrinologists, rheumatologists, gastroenterologists, and dermatologists have been prescribing biologics for at-home injection for many years. The best-known example, insulin, has been in use for nearly 100 years 24. At-home self-administration has the potential to reduce the burden on specialty clinics and allow physicians time to treat more patients with severe asthma.…”
Section: Discussionmentioning
confidence: 99%
“…High concentration human insulin is available at 500 U/mL. These high concentration insulins may offer benefits to certain patients because of their diverse pharmacological profiles and clinical characteristics 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…They were confident that their patients would be adherent to MTI treatment regimen when on IL200. Consistent with an overall assessment with concentrated insulins, this survey showed that IL200 was prescribed to patients with a wide range of insulin requirements [21,22]. The majority of patients taking IL200 were obese or overweight with T2DM and were likely to be severely insulin resistant.…”
Section: Discussionmentioning
confidence: 56%